The Structure of Liquid PbSiO3: Insight from Analysis and Visualization of Molecular Dynamics Data - Yen, Nguyen Van; Hong, Nguyen Van; Vinh, Le The (VNU Journal of Science: Mathematics - Physics; Vol 31 No 3, 2015)
The structural characteristics of liquid PbSiO 3 have been investigated by means of the molecular dynamics simulation. The simulations were done in a microcanonical ensemble, using pair potentials. Models consisting of 5000 atoms (1000 Pb, 1000 Si and 3000 O) were constructed at different pressures and at temperatures 3200 K. The local structure and network topology were analyzed through radial distribution function, bond angle distributions and coordination number distribution. The local environment around Pb atoms and continuity of silica and lead oxide sub-networks as well as their change under compression are also discussed in detail, moreover, we have used visualization techniques illustrated network structure. Keywords: Structural phase, liquid, triclusters, simulation, pressure.